School readiness and early literacy skills in english language in 4 to 5-year-old students at Academia Naval Guayaquil, school year 2019-2020 - Félix Ripalda, Karla Patricia (2020)
At early stages, children can get benefits from English language learning English. The most important is that the youngest the child, the better for them to learn. It happens because childhood is the optimal time to learn a language because when the child matures and the organization of the brain becomes more specialized, the ability to learn a language tends to decrease. The current study is directed to analyzed the influence of school readiness on early literacy skill in 4 to 5-year old students, and proposes the design of a teachers’ guide with school readiness activities to develop early literacy skills in English, in children. Chapter I describes topic of the current study, the background of the problem, the formulation and the systematization of the problem. The objectives, both broad and specific are described also in this section and are directed to analyze the influence of school readiness on early literacy skills in 4 to 5 year-old students at Academia Naval Guayaquil, School Year 2019-2020. The rationale included in this chapter emphasizes the importance, social relevance, beneficiaries and impact of the current study…………